2012
DOI: 10.1016/j.buildenv.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon: An overview on a perennial problem

Abstract: a b s t r a c tAccording to the World Health Organization (WHO) radon constitutes the second cause of lung cancer in the general population, the first being smoking. In addition health investigations also show that children are more susceptible than adults to ionizing radiation. In the past, it was accepted that only radon concentrations above 400 Bq/m 3 could constitute a health risk, however, recent epidemiological findings demonstrate lung cancer risk from exposure to indoor radon at levels in the order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Radon gas is known as the most important natural source of ionizing radiation and it is responsible for approximately 40% of the annual effective dose from all sources of radiation [13,14]. Epidemiological and toxicological studies have shown that long term exposure to radon increases the risk of lung cancer [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Radon gas is known as the most important natural source of ionizing radiation and it is responsible for approximately 40% of the annual effective dose from all sources of radiation [13,14]. Epidemiological and toxicological studies have shown that long term exposure to radon increases the risk of lung cancer [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Radon ( 222 Rn) is a colorless and odorless radioactive gas that has been strongly linked to deleterious human health outcomes, specifically lung cancer [1][2][3][4]. It is the most important source of ionizing radiation among those that are of natural origin, as it constitutes the second cause of death by lung cancer after tobacco [5].…”
Section: Introductionmentioning
confidence: 99%
“…The soil and building materials are the main sources of indoor radon [4,7,8], a natural radioactive gas that accumulates within buildings and consequently, is inhaled by their occupants [9,10].…”
Section: Introductionmentioning
confidence: 99%